{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

l12soln

# l12soln - CS 245 Winter 2009 Solution Set for Lecture 12...

This preview shows pages 1–3. Sign up to view the full content.

CS 245 Winter 2009 Solution Set for Lecture 12 Nissanke Ch. 9 1 Exercise 8.3 (p. 112) 1. (The text asks for informal proofs. Here formal proofs are provided using natural deduction.) Here we prove the material equivalence ( ) of the two formulas. The soundness of natural deduction allows us to conclude they are logically equivalent ( ). (a) | = ND x p ( x ) q ( x ) ( x p ( x )) ( x q ( x )) 1. x p ( x ) q ( x ) assumption 2. x u p ( x u ) q ( x u ) assumption 3. p ( x u ) assumption 4. x p ( x ) I 3 5. ( x p ( x )) ( x q ( x )) I 4 6. q ( x u ) assumption 7. x q ( x ) I 6 8. ( x p ( x )) ( x q ( x )) I 7 9. ( x p ( x )) ( x q ( x )) cases 2 , 3 5 , 6 8 10. ( x p ( x )) ( x q ( x )) E 1 , 2 9 11. ( x p ( x ) q ( x )) (( x p ( x )) ( x q ( x ))) I 1 10 12. ( x p ( x )) ( x q ( x )) assumption 13. x p ( x ) assumption 14. x u p ( x u ) assumption 15. p ( x u ) q ( x u ) I 14 16. x p ( x ) q ( x ) I 15 17. x p ( x ) q ( x ) E 13 , 14 16 18. x q ( x ) assumption 19. x u q ( x u ) assumption 20. p ( x u ) q ( x u ) I 19 21. x p ( x ) q ( x ) I 20 22. x p ( x ) q ( x ) E 18 , 19 21 23. x p ( x ) q ( x ) cases 12 , 13 17 , 18 22 24. (( x p ( x )) ( x q ( x ))) ( x p ( x ) q ( x )) I 12 23 25. (( x p ( x )) ( x q ( x ))) ( x p ( x ) q ( x )) I 11 , 24 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
(b) | = ND x • ¬ p ( x ) ⇔ ¬∃ x p ( x ) 1. x • ¬ p ( x ) assumption 2. x p ( x ) assumption 3. x u p ( x u ) assumption 4. ¬ p ( x u ) I 1 5. false ¬ E 3 , 4 6. false E 2 , 3 5 7. ¬∃ x p ( x ) RAA 2 6 8. x • ¬ p ( x ) ⇒ ¬∃ x p ( x ) I 1 7 9. ¬∃ x p ( x ) assumption 10. x g 11. p ( x g ) assumption 12. x p ( x ) I 11 13. false ¬ E 9 , 12 14. ¬ p ( x g ) RAA 11 13 15. x • ¬ p ( x ) I 10 14 16. ( ¬∃ x p ( x )) ( x • ¬ p ( x )) I 9 15 17. ( ¬∃ x p ( x )) ( x • ¬ p ( x )) I 8 , 16 (c) Are the following formulas logically equivalent? y •∃ x p ( x,y ) and x •∀ y p ( x,y ) No, they are not logically equivalent. To be logically equivalent, they must have
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}